2003
DOI: 10.1002/elps.200390086
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast analysis of oligosaccharides on microchip with light‐emitting diode confocal fluorescence detection

Abstract: We have developed a new method for the high-speed separation and high-sensitivity detection of complex oligosaccharides based on microchip electrophoresis (nu-CE) with light-emitting diode (LED) confocal fluorescence detection. Oligosaccharides labeled with 8-aminopyrene-1,3,6-trisulfonate (APTS) were found to strongly adsorb to the surface of polymethylmethacrylate (PMMA) microchips. Accordingly, three classes of major dynamic coating additives were systematically investigated, and cellulose derivatives were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 43 publications
(35 reference statements)
0
85
1
Order By: Relevance
“…Though the report demonstrated a miniaturized CE system, the separation capillary used was standard scale (48 m i.d.). And the LOD was slightly better than that quoted by Dang et al (19 nM for APTS-labeled glucose) using chipbased CE system [12].…”
Section: System Characteristicscontrasting
confidence: 53%
See 1 more Smart Citation
“…Though the report demonstrated a miniaturized CE system, the separation capillary used was standard scale (48 m i.d.). And the LOD was slightly better than that quoted by Dang et al (19 nM for APTS-labeled glucose) using chipbased CE system [12].…”
Section: System Characteristicscontrasting
confidence: 53%
“…In previous reports, the optical scheme of LED-FD is usually based on orthogonal configuration for eliminating the interference of excitation beam [3,4]. Some reports described the use of confocal configuration of LED-FD [11,12], but details were not given. Compared with above two schemes, collinear configuration has the advantages such as simple, compact and effective.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic coating methods were applied not only to control EOF and reduce analyte adsorption but also to make the hydrophobic PMMA surface more compatible with a hydrophilic separation medium. Dang et al [54] observed that the separation of oligosaccharides labeled with 8-aminopyrene-1,3,6-trisulfonate (APTS) in PMMA devices is impaired due to strong adsorption of the analytes to the PMMA surface. They systematically investigated different dynamic coating additives which were known to work well in classical CE using fused-silica capillaries.…”
Section: Polymethylmethacrylate Substratesmentioning
confidence: 99%
“…Tong and Yeung were the first to report the application of an absorption detection system for a CE separation based on red LEDs. 2 Since then, a number of different types of LED-induced fluorescence detectors for conventional CE [3][4][5][6][7][8] and microfluidic chip based CE [2][3][4] systems have been reported because they possess the advantages mentioned above. Lectins are proteins of non-immune origin that interact specifically with glycans without modifying them.…”
Section: Introductionmentioning
confidence: 99%